Nuclear magnetic resonance spectroscopy of liquid crystals - Dong, Ronald Y Ed (World Scientific, 2010)
"This edited volume provides an extensive overview of how nuclear magnetic resonance can be an indispensable tool to investigate molecular ordering, phase structure, and dynamics in complex anisotropic phases formed by liquid crystalline materials. The chapters, written by prominent scientists in their field of expertise, provide a state-of-the-art scene of developments in liquid crystal research." -- description from publisher's website.